Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Indigenous Perspectives on the Co-management of a Regional Conservation Area in the Peruvian Amazon - Natalia Arcos Cano; Michael P. Gilmore; Elizabeth Benson; Diego Valderrama; David Dimitrie; Brian M. Griffiths (Environmental Management, 2026)
Growing awareness of the critical role Indigenous Peoples and Local Communities (IPLCs) play in biodiversity conservation has underscored the need to shift conservation practices towards empowering IPLCs, supporting their land rights, traditional practices, and facilitating their political involvement. Despite IPLCs governing over 32% of global land, historically these communities have faced systemic marginalization and violence in the name of conservation. In response, international calls to action and policies have aimed to enhance IPLC participation in environmental governance through mechanisms like co-management. Adaptive Co-management (ACM) emerges as a promising approach, combining adaptive management’s flexibility with co-management’s collaborative principles. This study evaluates the ACM framework within the Maijuna-Kichwa Regional Conservation Area (MKRCA) in the Peruvian Amazon, established to protect the ancestral lands and biocultural resources of the Maijuna and Kichwa communities. Using a Community-Based Participatory Research (CBPR)-informed approach, we conducted interviews with 36 community members to assess their perspectives on the MKRCA’s co-management. Findings reveal significant improvements in resource abundance and community safety but also highlight issues with governmental support, communication, and equitable participation. Highly engaged participants voiced the strongest criticisms, underscoring how participation level shaped perceptions of governance. Recommendations were derived from participant perspectives but synthesized by the authors rather than fully co-developed. The study emphasizes the need for continuous evaluation and enhanced stakeholder engagement to optimize ACM’s effectiveness, offering culturally responsive recommendations to strengthen the MKRCA’s management and achieve its conservation objectives.

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Correction: Proposed highway in the Peruvian Amazon threatens vulnerable indigenous communities and natural protected areas - Brian M. Griffiths; David Dimitrie; Elizabeth Schierbeek; Edith Chinchilla Perez; Ellen Nirenblatt; Natalia Arcos Cano; Michael P. Gilmore (Ambio, 2026)

Patterns and thresholds for soil pH across Europe in relation to soil health and degradation - Inma Lebron; Christopher J. Feeney; Sabine Reinsch; Nima Shokri; Mehdi H. Afshar; Steve Lofts; Rob Griffiths; David Fidler; Briony Jones; Panos Panagos; Kasia Sawicka; Aidan M. Keith; et al. (CATENA, 2025)

Biodegradable mulch films exhibit slower-than-expected degradation with negligible effects on soil microbial communities - Martine Graf; Estelle Choiselat; Michaela K. Reay; Rafael Bargiela; Athanasios Dimitriou; Qiuyun Liu; Robert M. Elias; Peter N. Golyshin; Robert Griffiths; David R. Chadwick; Davey L. Jones (Journal of Hazardous Materials, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

Proposed highway in the Peruvian Amazon threatens vulnerable indigenous communities and natural protected areas - Brian M. Griffiths; David Dimitrie; Elizabeth Schierbeek; Edith Chinchilla Perez; Ellen Nirenblatt; Natalia Arcos Cano; Michael P. Gilmore (Ambio, 2025)
The conservation of biocultural diversity in the Amazon rainforest has become an international priority in the face of global change. Megadevelopment projects threaten conservation efforts and the rights of Indigenous communities to manage their ancestral lands. We examine the potential impacts of one proposed highway development project in the Peruvian Amazon, the Bellavista-El Estrecho Highway, on local and Indigenous communities and natural protected areas in the region. We found that zones of influence of the proposed highway eclipse 343 Indigenous communities of at least 33 000 Indigenous people of ten distinct cultures, 43 503 km 2 of community land, and 26 210 km 2 of natural protected areas including the entirety of the Maijuna–Kichwa Regional Conservation Area and the unique high terrace ecosystems it holds. Under international and national law in Peru, Indigenous communities who will be affected by megadevelopment projects like this highway must be engaged in prior consultation.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Mineralogic control on the calcium and magnesium stable isotopic compositions of modern microbial carbonates - Elizabeth M. Griffith; Matthew S. Fantle; Brittan V. Wogsland; Zijian Li; Majie Fan; David J. Wronkiewicz (Geochimica et Cosmochimica Acta, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Extremely low biodiversity Arctic intertidal habitats as sentinels for environmental change - Huw J. Griffiths; Catherine L. Waller; Stephen J. Roberts; Anna M. Jażdżewska; David S. Hik (Frontiers in Marine Science, 2024)
The Arctic is undergoing dramatic changes, including an unprecedented decline in sea ice. Previous studies have shown the severe structuring impact of sea ice scour upon polar intertidal communities. A dramatic example of the influence of Arctic sea ice is the highly depauperate intertidal of Cambridge Bay (Iqaluktuuttiaq) on Victoria Island, Nunavut, Canada. Cambridge Bay intertidal is dominated by a single species of amphipod crustacean, Gammarus setosus , with rare examples of another amphipod, bivalve molluscs, and oligochaetes. Primary producers are limited to a thin algal film, with no macroalgae present shallower than 2 m water depth. This intertidal biodiversity has remained extremely low since it was first surveyed 70 years ago, however, the seasonal sea ice thickness has been in decline for over 50 years. Given the observed dramatic increases in biodiversity and biomass with decreased sea ice cover elsewhere in the Arctic and the presence of the Canadian High Arctic Research Station, we suggest that the intertidal of Cambridge Bay offers an ideal location for a low cost, low effort, and long-term monitoring of biodiversity change and tipping points that may be influenced by sea ice loss in the Arctic as part of a network intertidal monitoring stations.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

A data‐driven approach to multiple‐stressor impact assessment for a marine protected area - Laura L. Griffiths; Joel Williams; Christina A. Buelow; Vivitskaia J. Tulloch; Mischa P. Turschwell; Max D. Campbell; David Harasti; Rod M. Connolly; Christopher J. Brown (Conservation Biology, 2024)
The coastal environment is not managed in a way that considers the impact of cumulative threats, despite being subject to threats from all realms (marine, land, and atmosphere). Relationships between threats and species are often nonlinear; thus, current (linear) approaches to estimating the impact of threats may be misleading. We developed a data‐driven approach to assessing cumulative impacts on ecosystems and applied it to explore nonlinear relationships between threats and a temperate reef fish community. We used data on water quality, commercial fishing, climate change, and indicators of recreational fishing and urbanization to build a cumulative threat map of the northern region in New South Wales, Australia. We used statistical models of fish abundance to quantify associations among threats and biophysical covariates and predicted where cumulative impacts are likely to have the greatest impact on fish. We also assessed the performance of no‐take zones (NTZs), to protect fish from cumulative threats across 2 marine protected area networks (marine parks). Fishing had a greater impact on fish than water quality threats (i.e., percent increase above the mean for invertivores was 337% when fishing was removed and was 11% above the mean when water quality was removed inside NTZs), and fishing outside NTZs affected fish abundances inside NTZs. Quantifying the spatial influence of multiple threats enables managers to understand the multitude of management actions required to address threats.

Effects of a mediterranean diet on the gut microbiota and microbial metabolites: A systematic review of randomized controlled trials and observational studies - Rachel Kimble; Phebee Gouinguenet; Ammar Ashor; Christopher Stewart; Kevin Deighton; Jamie Matu; Alex Griffiths; Fiona C. Malcomson; Abraham Joel; David Houghton; Emma Stevenson; Anne Marie Minihane; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Long-Term Drought and Warming Alter Soil Bacterial and Fungal Communities in an Upland Heathland - Fiona M. Seaton; Sabine Reinsch; Tim Goodall; Nicola White; Davey L. Jones; Robert I. Griffiths; Simon Creer; Andy Smith; Bridget A. Emmett; David A. Robinson (Ecosystems, 2022)
The response of soil microbial communities to a changing climate will impact global biogeochemical cycles, potentially leading to positive and negative feedbacks. However, our understanding of how soil microbial communities respond to climate change and the implications of these changes for future soil function is limited. Here, we assess the response of soil bacterial and fungal communities to long-term experimental climate change in a heathland organo-mineral soil. We analysed microbial communities using Illumina sequencing of the 16S rRNA gene and ITS2 region at two depths, from plots undergoing 4 and 18 years of in situ summer drought or warming. We also assessed the colonisation of Calluna vulgaris roots by ericoid and dark septate endophytic (DSE) fungi using microscopy after 16 years of climate treatment. We found significant changes in both the bacterial and fungal communities in response to drought and warming, likely mediated by changes in soil pH and electrical conductivity. Changes in the microbial communities were more pronounced after a longer period of climate manipulation. Additionally, the subsoil communities of the long-term warmed plots became similar to the topsoil. Ericoid mycorrhizal colonisation decreased with depth while DSEs increased; however, these trends with depth were removed by warming. We largely ascribe the observed changes in microbial communities to shifts in plant cover and subsequent feedback on soil physicochemical properties, especially pH. Our results demonstrate the importance of considering changes in soil microbial responses to climate change across different soil depths and after extended periods of time.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Novel compound heterozygous missense mutations in GDAP1 cause Charcot–Marie–Tooth type 4A - HUIQIN XUE; NEVEN MAKSEMOUS; DAVID SIDHOM; LAN MA; SHAOHUI CHEN; JIANRUI WU; YU FENG; LARISA M. HAUPT; LYN R. GRIFFITHS (Journal of Genetics, 2021)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Carbon flux and forest dynamics: Increased deadwood decomposition in tropical rainforest tree‐fall canopy gaps - Hannah M. Griffiths; Paul Eggleton; Nicole Hemming‐Schroeder; Tom Swinfield; Joel S. Woon; Steven D. Allison; David A. Coomes; Louise A. Ashton; Catherine L. Parr (Global Change Biology, 2021)
Tree mortality rates are increasing within tropical rainforests as a result of global environmental change. When trees die, gaps are created in forest canopies and carbon is transferred from the living to deadwood pools. However, little is known about the effect of tree‐fall canopy gaps on the activity of decomposer communities and the rate of deadwood decay in forests. This means that the accuracy of regional and global carbon budgets is uncertain, especially given ongoing changes to the structure of rainforest ecosystems. Therefore, to determine the effect of canopy openings on wood decay rates and regional carbon flux, we carried out the first assessment of deadwood mass loss within canopy gaps in old‐growth rainforest. We used replicated canopy gaps paired with closed canopy sites in combination with macroinvertebrate accessible and inaccessible woodblocks to experimentally partition the relative contribution of microbes vs. termites to decomposition within contrasting understorey conditions. We show that over a 12 month period, wood mass loss increased by 63% in canopy gaps compared with closed canopy sites and that this increase was driven by termites. Using LiDAR data to quantify the proportion of canopy openings in the study region, we modelled the effect of observed changes in decomposition within gaps on regional carbon flux. Overall, we estimate that this accelerated decomposition increases regional wood decay rate by up to 18.2%, corresponding to a flux increase of 0.27 Mg C ha −1 year −1 that is not currently accounted for in regional carbon budgets. These results provide the first insights into how small‐scale disturbances in rainforests can generate hotspots for decomposer activity and carbon fluxes. In doing so, we show that including canopy gap dynamics and their impacts on wood decomposition in forest ecosystems can help improve the predictive accuracy of the carbon cycle in land surface models.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Pre-treatment with microRNA-181a Antagomir Prevents Loss of Parvalbumin Expression and Preserves Novel Object Recognition Following Mild Traumatic Brain Injury - Brian B. Griffiths; Peyman Sahbaie; Anand Rao; Oiva Arvola; Lijun Xu; Deyong Liang; Yibing Ouyang; David J. Clark; Rona G. Giffard; Creed M. Stary (NeuroMolecular Medicine, 2019)

Comparison of Unyvero P55 Pneumonia Cartridge, in-house PCR and culture for the identification of respiratory pathogens and antibiotic resistance in bronchoalveolar lavage fluids in the critical care setting - Naomi J. Gadsby; Martin P. McHugh; Callum Forbes; Laura MacKenzie; Stephen K. D. Hamilton; David M. Griffith; Kate E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Correction to: Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Climate and soils together regulate photosynthetic carbon isotope discrimination within C 3 plants worldwide - William K. Cornwell; Ian J. Wright; Joel Turner; Vincent Maire; Margaret M. Barbour; Lucas A. Cernusak; Todd Dawson; David Ellsworth; Graham D. Farquhar; Howard Griffiths; Claudia Keitel; Alexander Knohl; et al. (Global Ecology and Biogeography, 2018)
Aim Within C 3 plants, photosynthesis is a balance between CO 2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO 2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO 2 drawdown during photosynthesis. Location Global Time period 1951–2011. Major taxa studied Vascular plants. Methods We assembled a database of leaf carbon isotope ratios containing 3,979 species–site combinations from across the globe, including 3,645 for C 3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO 2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO 2 concentrations at the site of carboxylation among plants in a given soil and climate.

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2016)
Skates and rays constitute the most speciose group of chondrichthyan fishes, yet are characterised by remarkable levels of morphological and ecological conservatism. They can be challenging to identify, which makes monitoring species compositions for fisheries management purposes problematic. Owing to their slow growth and low fecundity, skates are vulnerable to exploitation and species exhibiting endemism or limited ranges are considered to be the most at risk. The Madeira skate Raja maderensis is endemic and classified as ‘Data Deficient’ by the IUCN, yet its taxonomic distinctiveness from the morphologically similar and more wide-ranging thornback ray Raja clavata is unresolved. This study evaluated the sequence divergence of both the variable control region and cytochrome oxidase I ‘DNA barcode’ gene of the mitochondrial genome to elucidate the genetic differentiation of specimens identified as R. maderensis and R. clavata collected across much of their geographic ranges. Genetic evidence was insufficient to support the different species designations. However regardless of putative species identification, individuals occupying waters around the Azores and North African Seamounts represent an evolutionarily significant unit worthy of special consideration for conservation management.

Identification of motivational state in adult male Atlantic walruses inferred from changes in movement and diving behavior - Andrew D. Lowther; Kit M. Kovacs; David Griffiths; Christian Lydersen (Marine Mammal Science, 2015)
Motivational changes in animals are likely to be detectable retrospectively through observed changes in behavior. Breeding represents one of the strongest motivational states in mammals, and its timing is often tied to a seasonally optimal suite of environmental and physical conditions. While seasonal changes in behavior may be directly observable in some species, for others that breed cryptically or in difficult to access areas, detecting behavioral changes may only be feasible using data collected remotely. Herein, we explore whether behavioral changes can be used to infer motivational state for a wild, free‐ and wide‐ranging high arctic marine mammal, adult male Atlantic walruses ( Odobenus rosmarus rosmarus ). Using satellite‐relayed location and dive data from 23 adult male walruses instrumented in the Svalbard Archipelago, we identify seasonal movement to discrete geographic regions deep into winter pack ice. Adult male walrus diving behavior underwent marked seasonal movements between geographical areas that coincided with changes in light regime. At offshore wintering sites adult males ( n = 4) shifted from a summer pattern of deep, long benthic dives to much shallower diving. Some males performed similar shallow, winter dive behavior at coastal locations ( n = 12) suggesting that breeding might also occur around the coast of Svalbard. However, interpretation of behavioral changes of these coastal individuals was challenging. The presumed breeding sites at the winter off‐shore locations were situated in areas where polynyas are known to occur, making them a predictable resource even if they are located deep inside the winter pack‐ice. We demonstrate that remotely collected behavioral data can be used to identify seasonally explicit changes in the behavior of cryptic species.

Interpreting environmental change in coastal Alaska using traditional and scientific ecological knowledge - William G. Ambrose; Lisa M. Clough; Jeffrey C. Johnson; Michael Greenacre; David C. Griffith; Michael L. Carroll; Alex Whiting (Frontiers in Marine Science, 2014)

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Vaccine immunotherapy for prostate cancer: from mice to men - David M. Lubaroff; Daniel Vaena; James A. Brown; Pamela Zehr; Karen C. Griffith; Erica Brown; Julie Eastman; Kenneth Nepple; Ambika Kattula; Richard D. Williams (Immunologic Research, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Patterns, processes and vulnerability of Southern Ocean benthos: a decadal leap in knowledge and understanding - Stefanie Kaiser; Simone N. Brandão; Saskia Brix; David K. A. Barnes; David A. Bowden; Jeroen Ingels; Florian Leese; Stefano Schiaparelli; Claudia P. Arango; Renuka Badhe; Narissa Bax; Magdalena Blazewicz-Paszkowycz; et al. (Marine Biology, 2013)

A suggested new bacteriophage genus: “Viunalikevirus” - Evelien M. Adriaenssens; Hans-Wolfgang Ackermann; Hany Anany; Bob Blasdel; Ian F. Connerton; David Goulding; Mansel W. Griffiths; Steven P. Hooton; Elizabeth M. Kutter; Andrew M. Kropinski; Ju-Hoon Lee; Martine Maes; et al. (Archives of Virology, 2012)
We suggest a bacteriophage genus, “Viunalikevirus”, as a new genus within the family Myoviridae . To date, this genus includes seven sequenced members: Salmonella phages ViI, SFP10 and ΦSH19; Escherichia phages CBA120 and PhaxI; Shigella phage phiSboM-AG3; and Dickeya phage LIMEstone1. Their shared myovirus morphology, with comparable head sizes and tail dimensions, and genome organization are considered distinguishing features. They appear to have conserved regulatory sequences, a horizontally acquired tRNA set and the probable substitution of an alternate base for thymine in the DNA. A close examination of the tail spike region in the DNA revealed four distinct tail spike proteins, an arrangement which might lead to the umbrella-like structures of the tails visible on electron micrographs. These properties set the suggested genus apart from the recently ratified subfamily Tevenvirinae , although a significant evolutionary relationship can be observed.

Genome‐wide analysis of longevity in nutrient‐deprived Saccharomyces cerevisiae reveals importance of recycling in maintaining cell viability - Hazel M. Davey; Emma J. M. Cross; Christopher, L. Davey; Konstantinos Gkargkas; Daniela Delneri; David C. Hoyle; Stephen G. Oliver; Douglas B. Kell; Gareth W. Griffith (Environmental Microbiology, 2012)
Summary Although typically cosseted in the laboratory with constant temperatures and plentiful nutrients, microbes are frequently exposed to much more stressful conditions in their natural environments where survival and competitive fitness depend upon both growth rate when conditions are favourable and on persistence in a viable and recoverable state when they are not. In order to determine the role of genetic heterogeneity in environmental fitness we present a novel approach that combines the power of fluorescence‐activated cell sorting with barcode microarray analysis and apply this to determining the importance of every gene in the Saccharomyces cerevisiae genome in a high‐throughput, genome‐wide fitness screen. We have grown > 6000 heterozygous mutants together and exposed them to a starvation stress before using fluorescence‐activated cell sorting to identify and isolate those individual cells that have not survived the stress applied. Barcode array analysis of the sorted and total populations reveals the importance of cellular recycling mechanisms (autophagy, pexophagy and ribosome breakdown) in maintaining cell viability during starvation and provides compelling evidence for an important role for fatty acid degradation in maintaining viability. In addition, we have developed a semi‐batch fermentor system that is a more realistic model of environmental fitness than either batch or chemostat culture. Barcode array analysis revealed that arginine biosynthesis was important for fitness in semi‐batch culture and modelling of this regime showed that rapid emergence from lag phase led to greatly increased fitness. One hundred and twenty‐five strains with deletions in unclassified proteins were identified as being over‐represented in the sorted fraction, while 27 unclassified proteins caused a haploinsufficient phenotype in semi‐batch culture. These methods thus provide a screen to identifying other genes and pathways that have a role in maintaining cell viability.

Presence of Arundinaria gigantea (river cane) on numerous non-wetland sites suggests improper ecological classification of the species - Benjamin R. Tanner; David A. Kinner; Adam D. Griffith; Robert S. Young; Lee M. Sorrell (Wetlands Ecology and Management, 2011)

Characterisation of polymorphic microsatellite loci in the small-spotted catshark (Scyliorhinus canicula L.) - Andrew M. Griffiths; Didier Casane; Matthew McHugh; Victoria J. Wearmouth; David W. Sims; Martin J. Genner (Conservation Genetics Resources, 2011)

Levels of connectivity between longnose skate (Dipturus oxyrinchus) in the Mediterranean Sea and the north-eastern Atlantic Ocean - Andrew M. Griffiths; David W. Sims; Andrew Johnson; Arve Lynghammar; Matthew McHugh; Torkild Bakken; Martin J. Genner (Conservation Genetics, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Effects of Polyamine Synthesis Inhibitors on Primary Tumor Features and Metastatic Capacity of Human Breast Cancer Cells - Andrea Manni; Sharlene Washington; Xin Hu; James W. Griffith; Richard Bruggeman; Laurence M. Demers; David Mauger; Michael F. Verderame (Clinical & Experimental Metastasis, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Induced defences in an endangered amphibian in response to an introduced snake predator - Robin D. Moore; Richard A. Griffiths; Cliona M. O’Brien; Adam Murphy; David Jay (Oecologia, 2004)

Fluvial system response to Late Devensian (Weichselian) aridity, Baston, Lincolnshire, England - Rebecca M. Briant; G. Russell Coope; Richard C. Preece; David H. Keen; Steve Boreham; Huw I. Griffiths; Mary B. Seddon; Philip L. Gibbard (Journal of Quaternary Science, 2004)
Little is known about the impact of Late Devensian (Weichselian) aridity on lowland British landscapes, largely because they lack the widespread coversand deposits of the adjacent continent. The concentration of large interformational ice‐wedge casts in the upper part of many Devensian fluvial sequences suggests that fluvial activity may have decreased considerably during this time. The development of optically stimulated luminescence (OSL) dating enables this period of ice‐wedge cast formation to be constrained for the first time in eastern England, where a marked horizon of ice‐wedge casts is found between two distinctive dateable facies associations. Contrasts between this horizon and adjacent sediments show clear changes in environment and fluvial system behaviour in response to changing water supply, in line with palaeontological evidence. In addition to providing chronological control on the period of ice‐wedge formation, the study shows good agreement of the radiocarbon and OSL dating techniques during the Middle and Late Devensian, with direct comparison of these techniques beyond 15 000 yr for the first time in Britain. It is suggested that aridity during the Late Devensian forced a significant decrease in fluvial activity compared with preceding and following periods, initiating a system with low peak flows and widespread permafrost development. Copyright © 2004 John Wiley & Sons, Ltd.

Effects of α-difluoromethylornithine on local recurrence and pulmonary metastasis from MDA-MB-435 breast cancer xenografts in nude mice - Andrea Manni; Sharlene Washington; Laura Craig; Michael Cloud; James W. Griffith; Michael F. Verderame; Lindsay J. Texter; David Mauger; Laurence M. Demers; John F. Harms; Danny R. Welch (Clinical & Experimental Metastasis, 2003)

Development and Evaluation of a Macroinvertebrate Biotic Integrity Index (MBII) for Regionally Assessing Mid-Atlantic Highlands Streams - DONALD J. KLEMM; KAREN A. BLOCKSOM; FLORENCE A. FULK; ALAN T. HERLIHY; ROBERT M. HUGHES; PHILIP R. KAUFMANN; DAVID V. PECK; JOHN L. STODDARD; WILLIAM T. THOENY; MICHAEL B. GRIFFITH; WAYNE S. DAVIS (Environmental Management, 2003)

Influence of polyamines on in vitro and in vivo features of aggressive and metastatic behavior by human breast cancer cells - Andrea Manni; Sharlene Washington; James W. Griffith; Michael F. Verderame; David Mauger; Laurence M. Demers; Rajeev S. Samant; Danny R. Welch (Clinical & Experimental Metastasis, 2002)

Genetic dissection of collagen-induced arthritis in Chromosome 10 quantitative trait locus speed congenic rats: evidence for more than one regulatory locus and sex influences - Bina Joe; Elaine F. Remmers; David E. Dobbins; Jennifer L. Salstrom; Takefumi Furuya; Svetlana Dracheva; Pércio S. Gulko; Grant W. Cannon; Marie M. Griffiths; Ronald L. Wilder (Immunogenetics, 2000)